Translatio festi: The Mirror of Identities and Alterities in the Cult of St John of Trogir in the 15th c. - Marinković, Ana (2007)
The date of the major civic feast bears both symbolic meaning for the community, as well as the more pragmatical, economic aspect of it. The transfer of the feast date was quite a common practice, based on the cities' exigencies related to the trading cycle, but also to the political aspect of the cult. The paper is tracing the three parties (the noblemen, the clergy, the Venetian government) supporting three different proposals for the civic feast of Trogir, and the outcome of their intensive correspondence in the mid- fifteenth century.